Modelling the Relationship of Community of Inquiry and Critical Thinking Skills in Project-Based Learning with Digital Storytelling - Yulian, Ryani; Ruhama, Ufi; Yuniarti; Maulidya Raissa Insyira (LPPM Undiksha, 2025)
Teaching and learning effectiveness rely on multiple factors, including cognitive, social, and teaching dimensions. Although past research has looked into how the community of inquiry (CoI) affects learning, there is still limited knowledge about how CoI connects with project-based learning and digital storytelling. This study examined the connection between the community of inquiry (CoI) framework and critical thinking skills within project-based learningusing digital storytelling. Structural equation modelling (SEM) was employed to analyze the relationships among cognitive presence, social presence, and teaching presence (components of CoI), as well as their impact on engagement and critical thinking skills. Data were collected from 100 students engaged in a digital storytelling project through self-reported questionnaires on a Likert scale. The findings revealed that cognitive and social presences significantly affect student engagement and critical thinking, in line with the CoI framework. Conversely, teaching presence showed an insignificant relationship with engagement, indicating that in contexts that emphasize critical thinking, cognitive presence is more vital. This study highlights that while teaching presence can enhance emotional engagement and lower cognitive load, its role may be less prominent in activities focused on critical thinking. The results emphasize the need for context-specific strategies in applying the CoI framework to effectively develop critical thinking skills in project-based learning settings involving digital storytelling.